What infection control measures will people carry out to reduce transmission of pandemic influenza? A focus group study - Yardley Lucy; Morrison Leanne G (BMC, 2009)
Abstract Background Pandemic influenza poses a future health threat against which infection control behaviours may be an important defence. However, there is little qualitative research examining perceptions of infection control measures in the context of pandemic influenza. Methods Eight focus groups and one interview were conducted with a purposive sample of 31 participants. Participants were invited to discuss their perceptions of infection transmission and likely adherence to infection control measures in both non-pandemic and pandemic contexts. Infection control measures discussed included handwashing, social distancing and cough hygiene (e.g. covering mouth, disposing of tissues immediately etc.). Results Thematic analysis revealed that although participants were knowledgeable about infection transmission, most expressed unfavourable attitudes toward control behaviours in non-pandemic situations. However, with the provision of adequate education about control measures and appropriate practical support (e.g. memory aids, access to facilities), most individuals report that they are likely to adhere to infection control protocols in the event of a pandemic. Of the behaviours likely to influence infection transmission, handwashing was regarded by our participants as more feasible than cough and sneeze hygiene and more acceptable than social distancing. Conclusion Handwashing could prove a useful target for health promotion, but interventions to promote infection control may need to address a number of factors identified within this study as potential barriers to carrying out infection control behaviours.